2020
DOI: 10.1016/j.nicl.2020.102488
|View full text |Cite
|
Sign up to set email alerts
|

Emotional working memory training reduces rumination and alters the EEG microstate in anxious individuals

Abstract: Rumination is an important etiological factor of anxiety pathology, with its mechanism related to the deficit of working memory. The current study examined whether working memory training (WM-T) and emotional working memory training (EWM-T) could reduce rumination in anxious individuals. The participants with high trait anxiety underwent 21 days of mobile applications-based WM-T (n = 34), EWM-T (n = 36) or placebo control (n = 36), with questionnaires, cognitive tasks, and resting electroencephalogram (EEG) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 91 publications
(46 reference statements)
1
10
0
Order By: Relevance
“…aWMT arguably offered participants the opportunity to practice the mental manipulation of emotional stimuli, perhaps making it easier for these participants to mentally engage or disengage from or shift attention towards or away from negative emotional material (such as negative test-related thoughts or feelings), and consequently resulting in overall better mental control over such emotional stimuli ( du Toit et al, 2020 ). Moreover, affective WM shares the same frontoparietal neural circuitry as emotion regulation capacity; circuitry which has demonstrated improved efficiency following aWMT ( Pan et al, 2020 ; Schweizer et al, 2013 ). Given that TA can have a detrimental impact on an individual’s academic performance, implementing such simple and cost-effective cognitive training procedures as aWMT in educational settings may enable students to overcome symptoms of TA and perform to their highest potential in evaluative situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aWMT arguably offered participants the opportunity to practice the mental manipulation of emotional stimuli, perhaps making it easier for these participants to mentally engage or disengage from or shift attention towards or away from negative emotional material (such as negative test-related thoughts or feelings), and consequently resulting in overall better mental control over such emotional stimuli ( du Toit et al, 2020 ). Moreover, affective WM shares the same frontoparietal neural circuitry as emotion regulation capacity; circuitry which has demonstrated improved efficiency following aWMT ( Pan et al, 2020 ; Schweizer et al, 2013 ). Given that TA can have a detrimental impact on an individual’s academic performance, implementing such simple and cost-effective cognitive training procedures as aWMT in educational settings may enable students to overcome symptoms of TA and perform to their highest potential in evaluative situations.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this notion, Schweizer et al (2011) demonstrated that both aWMT and nWMT led to transfer gains on another WM task, however, only aWMT training produced transferable gains to improved affective control. Compared to control training, aWMT also led to improved regulation of emotional distress and altered recruitment in the brain regions underlying the successful control of affective information and states ( Pan et al, 2020 ; Schweizer et al, 2013 ). Beneficial effects of aWMT in clinical populations have also been observed ( du Toit et al, 2020 ; Krause-Utz et al, 2020 ; Schweizer et al, 2017 ; however see de Voogd et al, 2016 ).…”
mentioning
confidence: 99%
“…Indeed, we previously found a negative association between C microstates and self-oriented, verbal, and discontinuous patterns of thoughts associated with decreased self-reported levels of stress (Tomescu et al, 2022). In addition, Pan et al (2020) also found a negative association between microstate C and rumination level. The authors argue that microstate C might be a reliable index of ruminations (Pan et al, 2020).…”
Section: Discussionmentioning
confidence: 80%
“…In addition, Pan et al ( 2020) also found a negative association between microstate C and rumination level. The authors argue that microstate C might be a reliable index of ruminations (Pan et al, 2020). Ruminations are negative valence impulsive patterns of thoughts and an essential mind-wandering transdiagnostic factor in all mood disorders (McLaughlin & Nolen-Hoeksema, 2011;Pan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In both adolescents and adults, affective control has been found to account for variance in the association between self-reported emotion regulation and mental health, with the relationship between affective control, emotion regulation, and mental health being especially pronounced in younger adolescents (11-14 years;Schweizer et al, 2020b). Encouragingly, affective control is amenable to cognitive training, and such training has been shown to lead to improvements in emotion regulation and mental health outcomes (du Toit et al, 2020;Krause-Utz et al, 2020;Minihan et al, 2021b;Pan et al, 2020a;Pan et al, 2020b;Schweizer et al, 2013;Veloso & Ty, 2021;but see de Voogd et al, 2016). Improving affective control, particularly during adolescence, may therefore constitute a promising intervention target.…”
Section: Introductionmentioning
confidence: 99%